Desmopressin Has No Beneficial Effect on Excessive Postoperative Bleeding or Blood Product Requirements Associated with Cardiopulmonary Bypass - Prost, D de; Barbier-Boehm, G; Hazebroucq, J; Ibrahim, H; Bielsky, M C; Hvass, U; Lacombe, C; Français, J L; Desmonts, J M (Thrombosis and Haemostasis, 1992)
Cardiopulmonary bypass during open-heart surgery is sometimes associated with excessive perioperative bleeding. Following a non-randomized study suggesting that desmopressin acetate (desmopressin) reduced blood product requirements in these patients, we conducted a double-blind, placebo-controlled randomized trial of desmopressin (0.3 µg/kg, i. v.) in 92 patients with overt bleeding and a prolonged bleeding time.Mean blood loss during the first 24 h post-treatment was similar in the desmopressin and placebo groups (582 vs 465 ml, respectively; p = 0.15). Red-cell (p = 0.76), fresh frozen plasma (r = 0.66) and platelet unit (p = 0.74) requirements were also similar.The haemostatic effect of desmopressin has been attributed to the release of von Willebrand factor (vWF) and a reduced bleeding time. In our study, vWF and factor VIII :C levels increased while the bleeding time decreased significantly at 90 min and 24 h in both groups and, although vWF and factor VIII: C levels were slightly higher in desmopressin-treated patients at 90 min, the difference was not significant. Thrombin-antithrombin III complex, fibrinogen degradation product and tissue plasminogen activator levels, reflecting activation of the coagulation and fibrinolytic systems, respectively, decreased uniformely in both groups.We conclude that desmopressin is not useful in reducing blood loss or blood product requirements in patients with excessive immediate postoperative bleeding.